Negative Emotions and e-Learning Academic Performance of Engineering Students in a Private University - Fida Nirmala Nugraha; Zusy Aryanti; Tubagus Zulrizka Iskandar (International Journal of Innovation in Enterprise System, 2022)
One of the early pandemic COVID-19 effects on the educational sector is that learning activities needto be conducted fully online (e-learning). This circumstance can trigger negative emotions thatcontribute to students’ academic performance. This study aimed to find empirical data regarding therelationship of negative emotions and students academic performance in this particular situation. Thestudy was a cross-sectional quantitative method. Questionnaire of negative emotion (DASS-21)Indonesian version was deployed using google form to students of Industrial Engineering andInformation Systems class of 2020 using convenience sampling. 292 questionnaires were returnedand used. Findings: All three negative emotions (depression, anxiety, and stress) were experiencedby students at different levels. Negative emotions had different correlations to academic performance.There were no significant differences between anxiety and depression to students’ academicperformance (anxiety: F (3) = 2.202, ρ = 0.088, depression: F (2) = 1.397, ρ = 0.249). Two-wayANOVA showed that students who experienced mild stress performed better than those with normalstress category (F (1) = 3.933, ρ = 0.048). Female students significantly had better academicperformance compared to male students (ρ (0.001) < α= 0.05)) and that students experienced mildstress, performed better than those with normal stress category. Managing stress at a moderate levelis beneficial and can be done by media or counseling or other catharsis methods. Further study usinglarger samples from non engineering majors and randomized sampling is needed for generalizationas well as identifying factors that contribute to e-learning performance in a special situation.